2019
DOI: 10.1039/c8tc05130e
|View full text |Cite
|
Sign up to set email alerts
|

Interface disorder in large single- and multi-shell upconverting nanocrystals

Abstract: Single- and multi-shell upconverting nanocrystals, with their increasing numbers of applications, are characterized by core–shell and shell–shell interfaces, which are not yet fully understood. In this contribution, the magnitude of interface disorder in large single- and multi-shell nanocrystals is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…[132][133][134][135][136][137][138] Moreover, recent results showed that the cation intermixing in UCNPs was significant, 120,[139][140][141][142] resulting in the strong luminescence quenching through the deleterious CR processes between different Ln 3+ , supposedly located in the core or shell regions. 141,143 In addition, the concern of cation dopant distributions in nanostructures was addressed frequently. 142,[144][145][146] These issues not only perplex the detailed analysis of currently available results but also greatly prevent the explicit understanding of the overall quenching mechanism.…”
Section: Experimental Reproducibilitymentioning
confidence: 99%
“…[132][133][134][135][136][137][138] Moreover, recent results showed that the cation intermixing in UCNPs was significant, 120,[139][140][141][142] resulting in the strong luminescence quenching through the deleterious CR processes between different Ln 3+ , supposedly located in the core or shell regions. 141,143 In addition, the concern of cation dopant distributions in nanostructures was addressed frequently. 142,[144][145][146] These issues not only perplex the detailed analysis of currently available results but also greatly prevent the explicit understanding of the overall quenching mechanism.…”
Section: Experimental Reproducibilitymentioning
confidence: 99%
“…This result could be ascribed to core–shell intermixing caused by the relatively small core (8.6 nm) and whole core–multishell nanoparticle (20.6 nm), which is consistent with the previous report. 39–44…”
Section: Resultsmentioning
confidence: 99%
“…This intermixing process has been demonstrated, e.g., by TEM investigations. Examples are given by Hudry et al revealing an intermixing layer formed during the synthesis of core-shell nanostructures [ 10 , 11 , 12 , 13 ]. A recent work by Diogenis et al contributes to these findings and reveals a major excitation of Eu(III) in the core-shell interfacial region by an energy transfer from Gd(III) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%